2021
DOI: 10.7554/elife.72783
|View full text |Cite
|
Sign up to set email alerts
|

Working memory capacity of crows and monkeys arises from similar neuronal computations

Abstract: Complex cognition relies on flexible working memory, which is severely limited in its capacity. The neuronal computations underlying these capacity limits have been extensively studied in humans and in monkeys, resulting in competing theoretical models. We probed the working memory capacity of crows (Corvus corone) in a change detection task, developed for monkeys (Macaca mulatta), while we performed extracellular recordings of the prefrontal-like area nidopallium caudolaterale. We found that neuronal encoding… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 65 publications
0
25
0
Order By: Relevance
“…For example, the capacity of WM, the number of individual items that can be maintained simultaneously, is comparable between crows and macaque monkeys (Balakhonov & Rose, 2017). Even single neuron correlates of WM in birds are virtually identical to those in mammals (Ditz & Nieder, 2016Moll & Nieder, 2015;Rinnert et al, 2019;Rose & Colombo, 2005) and we recently found that this also extends to the neurophysiological limits of WM capacity (Buschman et al, 2011;Hahn et al, 2021).…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations
“…For example, the capacity of WM, the number of individual items that can be maintained simultaneously, is comparable between crows and macaque monkeys (Balakhonov & Rose, 2017). Even single neuron correlates of WM in birds are virtually identical to those in mammals (Ditz & Nieder, 2016Moll & Nieder, 2015;Rinnert et al, 2019;Rose & Colombo, 2005) and we recently found that this also extends to the neurophysiological limits of WM capacity (Buschman et al, 2011;Hahn et al, 2021).…”
Section: Introductionmentioning
confidence: 70%
“…4C) that simultaneously promotes selective neuronal activity without runaway excitation due to divisive normalization (Fries, 2015;Lundqvist et al, 2010). Together with analysis from single-neuron activity in crows (Hahn et al, 2021), it suggests that crow gamma could have a similar role in selection and normalization despite being implemented on a different neural substrate.…”
Section: Gamma Modulation Related To Wmmentioning
confidence: 87%
See 2 more Smart Citations
“…In birds, similar neurons have been described in the caudolateral nidopallium (NCL, Ditz and Nieder 2015). The NCL is believed to be an analogue of the PFC in the avian brain (Güntürkün et al 2021) and is involved in a variety of cognitive processes, including memory formation (Diekamp et al 2002, Hahn et al 2021, abstract rule learning (Veit and Nieder 2013), and action planning (Veit et al 2015).…”
Section: Introductionmentioning
confidence: 99%